Molecular docking reveals goldbandfish goatfish fatty acid's COX-2 inhibitory potential - Vincentius, Angelinus; Putra, Sukarman Hadi Jaya (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Goldbandfish goatfish, known for its high protein and fatty acid content, serves as a valuable food source contributing to human nutrition and well-being. This study delves into the potential anti-inflammatory properties of goldbandfish goatfish fatty acids, specifically palmitic acid, docosahexaenoic acid, and eicosapentaenoic acid, by targeting the inhibition of cyclooxygenase-2 (COX-2) protein. Through molecular docking experiments utilizing Molegro Virtual Docker version 5.0 and Discovery Studio version 21.1.1, the fatty acid structures were redocked with the COX-2 protein, with naproxen employed as a control COX-2 inhibitor. The analysis revealed interactions between the fatty acids and specific residues within the COX-2 inhibitor sites, mirroring the active sites targeted by naproxen, suggesting their potential as effective COX-2 blockers to mitigate inflammation. The findings suggest that the fatty acids present in goldbandfish goatfish possess promising anti-inflammatory effects through their ability to inhibit COX-2 activity. By binding to key residues within the COX-2 inhibitor sites, these fatty acids exhibit similarities to naproxen, a known COX-2 inhibitor. This study lays the groundwork for further investigations, including molecular dynamics simulations and in vitro experiments, to validate the anti-inflammatory efficacy of goldbandfish goatfish fatty acids and their potential as therapeutic agents for combating inflammation. The identification of natural compounds with COX-2 inhibitory properties opens avenues for the development of novel anti-inflammatory treatments derived from marine sources, contributing to the advancement of preventive and therapeutic strategies for inflammatory diseases.